Resilience as Predictor of Life Satisfaction and Mental Well-Being among Selected Southern University Students of Bangladesh (Bangladesh Journal of Psychology, 2024)
The study aimed to investigate how resilience affects young adults’ mental health and life satisfaction in Bangladesh. To achieve this end, a total number of 440 students were selected randomly from different universities situated in the southern part of Bangladesh. The Bangla version of the Resilience Scale for Adults (RSA), The Warwick Edinburg Mental Well-being Scale (WEMWBS), and the Satisfaction with Life Scale (SWLS) were administered to measure variables. Independent sample t-test, Pearson product-moment correlation and simple linear regression were performed to test the data. The results of the t-test revealed significant gender differences in life satisfaction, and correlation analysis revealed a significant positive correlation among resilience, mental well-being, and life satisfaction. Simple linear regression results revealed that 2.1% of the variability in life satisfaction and 29.8% of the variability in mental health were significantly predicted by resilience. This finding illustrates that increasing resilience will increase mental well-being and life satisfaction among university students in Bangladesh. Therefore, psychotherapy interventions that aim to strengthen psychological resilience and improve mental well-being may raise a person’s overall level of life satisfaction. Bangladesh Journal of Psychology Vol. 24, December 2024, pp. 49-60